ANALISIS MOTIVASI KERJA KARYAWAN PADA PT. ALFA KENCANA SAMUDRA - Nurhayati, Nurhayati (Jurnal Ekonomi Bisnis Kompetif, 2024)
Good quality human resources are very important for a company because it is a very common need for every company. This research uses a survey method using primary data obtained from questionnaires. The types of data used in this study are quantitative data and qualitative data. The results showed that work motivation was quite good, this can be seen from the responses of respondents at PT Alfa Kencana Samudra as many as 26 respondents based on this recapitulation, it can be concluded that the variable dimensions of physiological needs on work motivation at PT Alfa Kencana. This proves that PT Alfa Kencana Samudra has fulfilled the five needs of employees in the theory of needs put forward by Abraham Maslow (Mangkunegara, 2005) so that it can be concluded that employees are motivated to work. Keywords: Motivation, Work